Stakeholder discourse coalitions and polarisation in the hen harrier conservation debate in news media. Issue 2 (13th February 2023) - Marino, Filippo; Crowley, Sarah L.; Williams Foley, Nell A.; McDonald, Robbie A.; Hodgson, Dave J.
Abstract: Conservation conflicts are complex and can be deep‐rooted, with stakeholders holding entrenched policy positions. The actors involved producing verbal interconnected interactions that form policy debates. Thus, conservation debates can be viewed as network phenomena with stakeholders forming coalitions in support of, or opposition to, certain policies and practices. We used Discourse Network Analysis of print media to investigate the structure and dynamics of the stakeholder debate around the management of hen harriers Circus cyaneus, a bird of prey at the centre of a long‐standing conservation conflict in the United Kingdom. We aimed to determine whether the structure of discourse coalitions changed among the diverse aspects of the debate and whether the polarisation of the debate has changed through time. Our search and selection criteria led to the analysis of 737 statements within 131 newspaper articles published from August 1993 to December 2019. We show that, while the discourse network of the overall debate is quite unstructured, actors formed divergent coalitions when defining the conservation problem and its solutions. In contrast, discourses converged around reactions with positive or negative emotions in relation to events and issues of hen harrier conservation. Polarisation among actors has increased over time and peaked in the second half of the 2010s, concurrent with the release of the species recovery plan. Our study highlights the value of analysing discourse networks in conservation policy debates. Discourse networks reveal which aspects of any conservation problem cause stakeholders to converge or diverge and can identify periods of intensified debate that, ultimately, contribute to informing conflict mitigation and resolution processes. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Sommario: I conflitti sulla conservazione sono complessi e possono essere profondamente radicati, con portatori di interesse che mantengono posizioni politiche consolidate. Gli attori coinvolti producono interazioni verbali interconnesse che formano dibattiti politici. Perciò, i dibattiti sulla conservazione possono esser visti come fenomeni network (reti sociali) dove le parti interessate formano coalizioni in supporto, o in opposizione, a determinate politiche e pratiche. Abbiamo utilizzato una Discourse Network Analysis della carta stampata per indagare la struttura e le dinamiche del dibattito tra i portatori di interesse riguardo la gestione dell'albanella reale Circus cyaneus, un rapace al centro di un conflitto di conservazione di lunga data nel Regno Unito. Abbiamo mirato a determinare se la struttura delle coalizioni di discorso è cambiata nei diversi aspetti del dibattito e se la polarizzazione del dibattito è cambiata nel tempo. I nostri criteri di ricerca e selezione hanno portato all'analisi di 737 dichiarazioni in 131 articoli di giornale pubblicati da agosto 1993 a dicembre 2019. Mostriamo che, mentre il network dell'intero dibattito è piuttosto destrutturato, gli attori hanno formato coalizioni che divergono nel definire la questione della conservazione e le sue soluzioni. Al contrario, i discorsi convergevano attorno a reazioni con emozioni positive o negative in relazione ad eventi e problemi associati alla conservazione dell'albanella reale. La polarizzazione tra gli attori è aumentata nel tempo e ha raggiunto il picco nella seconda metà degli anni 2010, in concomitanza con la pubblicazione del piano di recupero delle specie. Il nostro studio evidenzia il valore dell'analizzare i network del discorso nei dibattiti sulle politiche per la conservazione. Le reti di discorso rivelano quali aspetti della conservazione fanno convergere o divergere le parti interessate e possono identificare periodi di forte dibattito che, in ultima analisi, contribuiscono a informare i processi di mitigazione e risoluzione dei conflitti.